Upregulation of prolylcarboxypeptidase (PRCP) in lipopolysaccharide (LPS) treated endothelium promotes inflammation - Kolte Dhaval; Mahdi Fakhri; Ngo My-Linh; Shariat-Madar Zia (BMC, 2009)
Abstract Background Prolylcarboxypeptidase (Prcp) gene, along with altered PRCP and kallikrein levels, have been implicated in inflammation pathogenesis. PRCP regulates angiotensin 1-7 (Ang 1-7) - and bradykinin (BK) - stimulated nitric oxide production in endothelial cells. The mechanism through which kallikrein expression is altered during infection is not fully understood. Investigations were performed to determine the association between PRCP and kallikrein levels as a function of the upregulation of PRCP expression and the link between PRCP and inflammation risk in lipopolysaccharide (LPS)-induced endothelium activation. Methods The Prcp transcript expression in LPS-induced human umbilical vein endothelial cells (HUVEC) activation was determined by RT-PCR for mRNA. PRCP-dependent kallikrein pathway was determined either by Enzyme Linked ImmunoSorbent Assay (ELISA) or by biochemical assay. Results We report that PRCP is critical to the maintenance of the endothelial cells, and its upregulation contributes to the risk of developing inflammation. Significant elevation in kallikrein was seen on LPS-treated HUVECs. The conversion of PK to kallikrein was blocked by the inhibitor of PRCP, suggesting that PRCP might be a risk factor for inflammation. Conclusion The increased PRCP lead to a sustained production of bradykinin in endothelium following LPS treatment. This amplification may be an additional mechanism whereby PRCP promotes a sustained inflammatory response. A better appreciation of the role of PRCP in endothelium may contribute to a better understanding of inflammatory vascular disorders and to the development of a novel treatment.